Psychological Symptoms in Young Adult Migraineurs - Akalin, Turgay; Sinal, Aysin (Mediterranean Journal of Social Sciences, 2020)
We aimed to reveal psychological symptoms of young university students (18-25 y/o) with no secondary disease with complaints of migraine headaches. We compared the psychological symptoms with a young control group that did not present headaches and other studies examining migraines in different age groups to determine any similarities. The study consisted of 75 migraine cases; 13 with aura and 62 without aura) and 42 non-headache control subjects. The International Classification of Headache Disorders 3 (ICHD-3) with criteria questions and the Psychological Symptom Research Scale were applied to all participants and SPSS Statistics Program evaluated the data. Findings: 1) In the test of Descriptive Statistics for the Sample of Students, average values of both sexes were taken and found the average values of the migraine groups were higher than control group. 2) The Anova Test found differences in the diagnostic group besides depression (Somatisation p<., others p<.01) with no significant difference in depression (p=0.315). 3)The Pearson Correlation Analysis, found no association between age and psychological symptoms. There’s a significant relationship between psychological symptoms with somatisation (besides paranoid) (p<.05). There’s a significant relationship between depression and other psychological symptoms (p<.05). There’s a significant relationship between anxiety, obsession, interpersonal relationships, psychoticism, paranoia, anger, phobia, additional scale and other psychological symptoms (p<.01). Result: The study demonstrated psychological symptoms in young migraineurs. The average psychological symptoms of both migraine groups were higher than the control group, this showed psychological symptom similarities between young migraineurs and migraine patients of different age groups.